Correlation between Financial Difficulties and Financing Strategies among Market Stallholders in Batangas City - Ilagan, Amor A (Financial Risk and Management Reviews, 2019)
The aim of this study was to determine the correlation between financial difficulties and financing strategies among market stallholders in Batangas City. Specifically, the study sought to determine the profile of the respondents in terms of age, sex, civil status, highest educational attainment, market section, number of years in operation, average monthly business income and stall location. The researcher also assessed the financial difficulties experienced by market stallholders and the extent of utilization of financing strategies in terms of internal financing and debt financing. Moreover, the researcher also determined the correlation between financial difficulties and financing strategies, the significant difference on the financial difficulties experienced by market stallholders and extent of utilization of financing strategies of the respondents when grouped according to profile variables. The findings of the study revealed that there is a correlation between financial difficulties and internal financing and another correlation between financial difficulties and debt financing utilized by market stallholders. An extension activity was proposed as an output of this study so that market stallholders would understand the different financing strategies banks and other microfinancing institutions are offering.